Identity, hybridity and cultural home Chinese migrants and diaspora in multicultural societies - Liu, Shuang 1959- (Rowman & Littlefield International, 2015)
"Explores identity formation and cultural home for generations of Chinese immigrants living in multicultural societies across the world"--Publisher.